Gender and care : overview report - Esplen, Emily (Bridge BrightonGB, 2009)
Explores the range of activities that constitute care, both paid and unpaid. Discusses the reason why care matters for poverty reduction and gender equality. Looks at two strategies needed to bring about more equitable and effective ways of providing care. Focuses on how to deal with the challenges of providing care in the context of HIV and AIDS. Considers the measures needed to protect the rights of paid care workers, particularly domestic workers.